2011
DOI: 10.1074/jbc.m110.186684
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Impairs the Induction of Cytoprotective Nrf2 Target Genes by Delocalization of Small Maf Proteins

Abstract: The expression of a variety of cytoprotective genes is regulated by short cis-acting elements in their promoters, called antioxidant response elements (AREs). A central regulator of ARE-mediated gene expression is the NF-E2-related factor 2 (Nrf2). Nrf2/ARE-regulated genes are crucial for the maintenance of cellular integrity. Hepatitis C virus inhibits the induction of ARE-regulated genes, but neither induction nor inhibition of ARE-regulated gene expression affects HCV replication directly. In HCV-replicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 43 publications
4
84
1
1
Order By: Relevance
“…In line with this observation, we found ALR expression induced in HBV-infected, but not in HCV-infected, cells in vitro and in vivo (Figures 4, 5), which is in agreement with some recent findings reporting a HCVdependent inhibition of Nrf2/AREregulated genes (11). In addition, it was reported that Nrf2 protects from toxininduced liver injury and fibrosis (9), which seems to be contradictory to chronic HBV infection as a causative factor for liver fibrosis, cirrhosis or HCC.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…In line with this observation, we found ALR expression induced in HBV-infected, but not in HCV-infected, cells in vitro and in vivo (Figures 4, 5), which is in agreement with some recent findings reporting a HCVdependent inhibition of Nrf2/AREregulated genes (11). In addition, it was reported that Nrf2 protects from toxininduced liver injury and fibrosis (9), which seems to be contradictory to chronic HBV infection as a causative factor for liver fibrosis, cirrhosis or HCC.…”
supporting
confidence: 81%
“…Activation of Nrf2 followed by expression of ARE-regulated genes was not only shown for chemopreventive and antioxidant agents, but also reported to be mediated by hepatitis B virus (HBV) (10), while hepatitis C virus (HCV) inhibits Nrf2 activation (11). Therefore, we analyzed the potential impact of HBV and HCV infection on ALR expression in vitro and in vivo.…”
Section: Alr Expression Is Enhanced In Hbv-positive Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…4e7 Several mechanisms normally protect the liver from alcoholic injury, and these include antioxidant enzymes, such as superoxide dismutase 8 and thioredoxin. 9 HCV can impair antioxidant defenses by decreasing activation of nuclear factor erythroid 2-related factor 2 (Nrf-2) 10 and heme oxygenase-1, 11 two important components of the antioxidant response, and these have been postulated to play a role in ethanol-HCV synergy. 11 Understanding the mechanisms by which these occur could, therefore, lead to novel prophylactic and therapeutic approaches to alcoholic liver disease.…”
mentioning
confidence: 99%
“…This is not surprising as similar results were seen in OFI group, but in contrast, during DOD the Nox-2 gene expression was found to increase in dengue cases whereas no such hike was observed in OFI, which makes us to assume if the increase in Nox-2 during DOD is 'specific' for dengue infection. Monica et al [4] studied that during Hepatitis C virus infection delocalization of sMAF proteins caused the formation of Nrf-2-sMAF complex which in turn blocked Nrf2 translocation and ultimately caused transcriptional inactivation of detoxifying enzymes. This could be a possible mechanism for down regulated Nrf2 expression during day of admission.…”
Section: Discussionmentioning
confidence: 99%